y squared +12y+35
2006-11-01 15:48:45
·
answer #1
·
answered by lollipop 3
·
1⤊
0⤋
Try the FOIL method (First, Outer, Inner, and Last):
(y*y)+(7*y)+(5*y)+(7*5)=
y^2+7y+5y+35=
y^2+12y+35
I hope that is helpful!
2006-11-01 23:50:11
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(y+5)(y+7)
= y^2+7y+5y+35
=y^2+12y+35
2006-11-02 09:07:45
·
answer #3
·
answered by mini_gal 3
·
0⤊
0⤋
are we multipying or solving?
y+5=0
y= -5
y+7=0
y= -7
To multiply we must FOIL
multiply the First two, the Outside two, the Inside two, then the Last two
(y+5)(y+7)
y^2 + 7t + 5y +35
now combine the like terms
y^2 +12y +35
and you're done
2006-11-01 23:53:14
·
answer #4
·
answered by ineedonebuddy 3
·
0⤊
0⤋
FOIL:
Firsts : y*y
Outers: y*7
Inners: 5*y
Lasts: 5*7
So: y*y + y*7 + 5*y + 5*7
Equals: y^2 + 7y + 5y + 35
Equals: y^2 + 12y + 35.
2006-11-01 23:50:10
·
answer #5
·
answered by topher8128 2
·
1⤊
0⤋
= y^2 + 12y +35
2006-11-01 23:47:59
·
answer #6
·
answered by kellenraid 6
·
1⤊
0⤋
y^2 + 12y + 35
2006-11-01 23:47:27
·
answer #7
·
answered by jacinablackbox 4
·
1⤊
0⤋